Effect of comonomer of methacrylic acid on flexural strength and adhesion of Staphylococcus aureus to heat polymerized poly (methyl methacrylate) resin: An in vitro study - Lokendra Gupta; I N Aparna; Sujatha Bhat; Kishore Ginjupalli (Wolters Kluwer Medknow Publications, 2017)
Aims and Objective: The purpose of the present study was to evaluate and compare flexural strength and Staphylococcus aureus adhesion of heat-activated poly (methyl methacrylate [MMA]) resin modified with a comonomer of methacrylic acid (MAA) and MMA monomer. Materials and Methods: Comonomer preparation was done with the addition of varying concentration of MAA (0, 15, 20, and 25 wt %) to the MMA of conventional heat-activated denture base resin to prepare the specimens. Prepared specimens were stored in distilled water at 37°C for 1 day and 1 week before the evaluation of flexural strength and microbial adhesion. Flexural strength was measured using a universal testing machine at a crosshead speed for 2 mm/min (n = 10). Microbial adhesion (colony-forming unit [CFU]) was evaluated against S. aureus using a quadrant streaking method (n = 5). Data were subjected to one-way ANOVA, and the significant differences among the results were subjected to Tukey's HSD test. P < 0.05 was considered statistically significant. Results: Addition of MAA to the MMA monomer was found to significantly reduce the adhesion of S. aureus for all the groups. Reduction of CFU of S. aureus was found be more significant for Group 3 as compared to control, both at 1-day (P < 0.001) and 1-week (P < 0.002) storage in distilled water. However, no statistically significant changes in the flexural strength were observed with the addition of MAA at 1-day (P = 0.52) and 1-week (P = 0.88) time interval. Conclusion: Addition of MAA to conventional denture base resin reduced the microbial adhesion without significantly affecting the flexural strength.